Perbedaan Pengetahuan Sebelum dan Sesudah Penyuluhan tentang Sex Education Pada Siswa di SMA Negeri 1 Kampar Timur Provinsi Riau - Tyagita Widya Sari; Putri Octia Hairani (Journal of Indah Science and Clinic, 2021)
According to WHO in 2014, Sex Education is a provider of information on body development, sex, sexuality, relationships, accompanied by skills and education to help adolescents interact and make decisions that include sex and sexual health. A preliminary study at SMA Negeri 1 Kampar Timur obtained information that every semester there are students who drop out because they are pregnant out of wedlock, and there has never been any counseling about Sex Education. The aim is to determine the knowledge before and after the Sex Education intervention on students at SMAN 1, East Kampar. Pre Experimental Design with One Group Pre and Post Test Design was used in the research. Accidental sampling was used to take a sample of 50 people. Questionnaire data were collected before and after the intervention. The univariate and bivariate analysis used the Wilcoxon Test. The results showed a significant difference in knowledge before and after the intervention (p < 0.05). Differences in knowledge exist before and after the Sex Education intervention of students at SMA Negeri 1 Kampar Timur.